EQUAL EMPLOYMENT PADA REKRUTMEN DOSEN DI STIE ISLAM BUMIAYU - Suwarjono Suwarjono (JBIMA (Jurnal Bisnis dan Manajemen), 2013)
The research used qualitative descriptive method. The kind of the research was able to cover various qualitative information needed with full of nuance on it. The strategy of the research was used survey; it was a kind of the research method that aimed to collect huge variables about an individual number through some interviews and questionnaires.The source of the research data comprised (a) the previous studies, (b) informant, namely: all of the stakeholders who got involved such as: head of institute foundation, management of STIE, lecturers, lecturers’ applicant and some workers, (c) questionnaires.The technique of collecting data was used (1) technique of the previous studies to analyze all of the theories about worker on each institution and enterprise, (2) interview, by giving some open questions, (3) questionnaires, by disseminating to some informants to get the complete and accurate data.According to the observation through the questionnaire, the writer had examined that the recruitment of the lecturer did not requisite to the sex of the lecturer, as it has been listed to the requirement of the personnel regulation. It could be seen to the table data of STIE Islam Bumiayu’s lecturers in the academic year 2011/2012. There were 24 lecturers (5 female lecturers and 19 male lecturers). It caused that the foundation of Ta’allumul Huda Bumiayu had a principle to lecturers’ consignation based on the monotheism, humanist, nationalist, democracy, and social justice.